SEPARATION OF UP GOING AND DOWN GOING WAVES IN VSP USING SINGULAR VALUE DECOMPOSITION - Suprajitno Munadi; Lasmi Kustiowati; Moh. Bunjamin (Testing Center for Oil and Gas LEMIGAS, 1991)
The separation of upgoing and downgoing waves in Vertical Seismic Profiling (VSP) is effectively accomplished using the singular value decomposition method. The VSP data can be decomposed into eigenimages which is directly proportional to the singular value.